2018
DOI: 10.2147/ijn.s154968
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the translocation mechanism of PLGA nanoparticles across round window membrane into the inner ear: a guideline for inner ear drug delivery based on nanomedicine

Abstract: Background The round window membrane (RWM) functions as the primary biological barrier for therapeutic agents in the inner ear via local application. Previous studies on inner ear nano-drug delivery systems mostly focused on their pharmacokinetics and distribution in the inner ear, but seldom on the interaction with the RWM. Clarifying the transport mechanism of nanoparticulate carriers across RWM will shed more light on the optimum design of nano-drug delivery systems intended for meeting demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
(39 reference statements)
1
29
0
Order By: Relevance
“…The caveolin-1 signaling pathway is known for its role in regulating cellular functions, including signal transduction and endocytosis. 26 Zhang et al 27 prepared PLGA NPs encapsulating coumarin-6 and analyzed the endocytic mechanism of NPs through this membrane interface by means of various endocytic inhibitors. The results showed that NPs were internalized predominantly via macropinocytosis and caveolin-mediated endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The caveolin-1 signaling pathway is known for its role in regulating cellular functions, including signal transduction and endocytosis. 26 Zhang et al 27 prepared PLGA NPs encapsulating coumarin-6 and analyzed the endocytic mechanism of NPs through this membrane interface by means of various endocytic inhibitors. The results showed that NPs were internalized predominantly via macropinocytosis and caveolin-mediated endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the drug will accumulate in cochlea at only a low concentration; therefore, many methods are currently being investigated to improve the permeability of the RWM for local drug delivery. Some efficient carriers such as poly (lactic-co-glycolic acid) nanoparticles and phospholipid-based nanoparticles are used as inner ear nanoparticulate carriers to produce better therapeutic effects and to maintain long-term particle circulation in the perilymph (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Permeability was increased by a factor of 2–3 for the higher drug concentration [ 111 ]. This behaviour has also been presented in Poly (lactic- co -glycolic acid) (PLGA) nanoparticles [ 116 ]. An increased contact duration of a solution with the RWM subsequently increases its permeability, as shown with PLGA nanoparticles [ 116 ] and TMPA solution [ 111 ].…”
Section: Local Drug Delivery Of Antioxidants To Inner Earmentioning
confidence: 73%